How computer games help children learn - Shaffer, D (How Computer Games Help Children Learn, 2007)
In this trailblazing book, leading educational expert David Shaffer examines how particular video and computer games can help teach kids to think like doctors, lawyers, engineers, urban planners, journalists and other professionals. Based on more than a decade of research in technology, game science, and education, this book revolutionizes how we think about education in the digital age. (DIPF/Orig.).